Diaries in intensive care units: An Italian qualitative study. Issue 1 (30th May 2021) - Negro, Alessandra; Villa, Giulia; Zangrillo, Alberto; Rosa, Debora; Manara, Duilio F.
Abstract: Background: The literature emphasizes the importance of the intensive care unit (ICU) diary to fill the gaps and recover the delusional memories of patients admitted to ICU in order to build the history of their illness. The ICU diary is a measure originally intended to support the severely ill patient, but it would also seem to be useful for family members and carers. According to our analysis of the literature, this study is the first description of the contents of ICU diaries in the Italian context. Aim: The aim of the study was to describe the contents of ICU patients' diaries filled in by their caregivers, in order to explore the experience and significance attributed to the diaries. Design: A qualitative longitudinal narrative investigation was conducted at an ICU during the period from April 2016 to April 2017 with a sample composed of 32 families. Methods: The participants were caregivers selected through purposive sampling. An ICU nurse explained the study to caregivers and offered the opportunity to participate. Results: The sample included 32 diaries. Through the analysis we identified seven themes: future plans and memories; the people who care for the patient and the context; the love surrounding the patient; the clinical progression of the patient and the passage of time; what happens outside the patient's life; references to the usefulness/non‐usefulness of the diary; communication/reflection on the likely death of the patient. Conclusions: Some themes emerged that have never explored in the literature, and it would be necessary to understand whether the themes that emerged depend on cultural issues. Relevance to clinical practice: The diaries could be adapted to the Italian context and this could make the diary a common practice in Italy as well.